Review of Mucuna pruriens L. therapeutic potential for Parkinson’s disease - A. S. Panova; D. S. Dergachev; M. A. Subotyalov; V. D. Dergachev (Медицинский совет, 2020)
Parkinson’s disease is a multifactorial disorder of the nervous system, the main features of which are progressive degeneration of dopaminergic neurons in the nigra pars compacta nigrostriatal tract and subsequent deficiency of the neurotransmitter dopamine in the areas of the brain, leading to the loss of motor function, the emergence of non-motor symptoms, rigidity, akinesia or bradykinesia, motor block, and decline in cognitive functions. Parkinson’s disease has high prevalence throughout the world, and has no curative treatment in modern medicine. The available drugs such as anticholinergics, levodopa and a DOPA-decarboxylase inhibitor provide symptomatic relief only. Although dopaminergic therapy is the standard treatment of motor disabilities associated with Parkinson’s disease, it does not managed all the aspects of the disease. For this reason, the increasing numbers of patients are looking for more holistic approach to the treatment of this disease. Mucuna pruriens L. – an annual self-pollinating legume plant, can be considered as a potential complementary therapy for patients with Parkinson’s disease, as it is an extremely rich source of levodopa. Numerous studies have shown that Mucuna pruriens extracts restore biochemical and behavioral abnormalities in animals with the experimental model of Parkinson’s disease. The plant also demonstrates some antioxidant activity. The clinical effects of high-dose Mucuna pruriens are similar to levodopa, but have a more favorable tolerance profile. If long-term use of Mucuna pruriens proves safe and effective in controlled clinical trials, it could become a sustainable complementary therapy for the treatment of Parkinson’s disease, especially in low-income countries.